Quantitative Analysis of the Debris Flow Societal Risk to People Inside Buildings at Different Times: A Case Study of Luomo Village, Sichuan, Southwest China - Wei, Li; Hu, Kaiheng; Liu, Jin (Frontiers in Earth Science, 2021)
Debris flows, which cause massive economic losses and tragic losses of life every year, represent serious threats to settlements in mountainous areas. Most deaths caused by debris flows in China occur in buildings, and the death toll is strongly dependent on the time people spend indoors. However, the role of time spent indoors in the quantitative analysis of debris flow risk has been studied only scarcely. We chose Luomo village in Sichuan atop a debris flow alluvial fan to study the influence of the temporal variation in the presence of people inside buildings on the societal risk. Two types of days (holidays vs. workdays) and two diurnal periods (daytime vs. nighttime) were considered in our risk evaluation model. A questionnaire survey was conducted for each family in the village, and the probability of the temporal impact of a debris flow on every household was calculated based on the average amount of time each member spent in the house. The debris flow hazard was simulated with FLO-2D to obtain the debris flow intensity and run-out map with return periods of 2, 10, 50, and 100 years. The risk to buildings and societal risk to residents were calculated quantitatively based on the probabilities of debris flow occurrence, the probability of the spatial impact, and the vulnerabilities of buildings and people. The results indicated that societal risk on holidays is always higher than that on weekdays, and societal risk at night is also much higher than that in the daytime, suggesting that the risk to life on holidays and at night is an important consideration. The proposed method permits us to obtain estimates of the probable economic losses and societal risk to people by debris flows in rural settlements and provides a basis for decision-making in the planning of mitigation countermeasures.